Analisis Implementasi Pascaban Amandemen Tahun 2019 Konvensi Basel di Kota Batam Mengenai Pelarangan Impor Sampah Plastik - Vatdra, Thassya; Anita Afriani Sinulingga; Putriviola Elian Nasir (Hubungan Internasional Universitas Andalas, 2022)
This study aims to describe the implementation of the Ban Amendment to the Basel Convention in 2019 in Batam. Batam city is one of the cities that has a port that has been designated as a point of entry and exit for the import of non-B3 waste and/or waste. This situation led to the discovery of many imports of B3 waste and/or waste, especially plastic waste, which peaked in 2019. In this study, the researcher uses the concept of regime implementation at the domestic level, which analyzes the behavior of social actors in implementing regime provisions at the domestic level by the provisions of the regime. Data collection and analysis were carried out using qualitative methods and descriptive-analysis approaches. Researchers found that social actors involved in implementing the Basel Convention in Batam city, especially regarding the prohibition of the importation of B3 waste still have not fully participated in realizing the country's targets that comply with the provisions of the regime.